The relationship between human resource management practices and organizational citizenship behaviour - Ravikumar, Guhamani (2024)
The performance of employees is crucial to organizational success, and one key factor influencing Organizational Citizenship Behaviour (OCB) is Human Resource Management Practices (HRMP). This study aims to investigate the relationship between HRMP and OCB by examining six HRMPs: recruitment and selection, training and development, compensation and benefits, performance appraisal, involvement, and work conditions by utilizing Social Exchange Theory to understand the relationship mechanism. A quantitative approach is employed with the Statistical Package for the Social Sciences (SPSS) software (Version 26) for data analysis. The analysis includes reliability testing, descriptive analysis, correlation analysis, and multiple regression analysis, providing robust insights into the research question. The study involves 448 employees from four major glove manufacturers. The findings reveal a significant relationship between HRMP and OCB, with HRMP accounting for 65 per cent of the variance in OCB. This research contributes to the existing body of knowledge on HRMP and OCB among glove manufacturing employees, highlighting the importance of HRMP in fostering OCB. The findings offer new insights for glove manufacturing employers on effectively utilizing HRMP to promote OCB within their organizations.